DINAMIKA ELIT LOKAL DI ACEH TERHADAP PENGUASA - Taqwadin, Danil Akbar (Al-Ijtima`i: International Journal of Government and Social Science, 2020)
The history of Aceh in the last century is a cycle of conflict and peace. The presence of conflict and peace is also inseparable from the involvement of the authorities, both during the colonial period and the Aceh compilation which had joined Indonesia. In this case, the ruler does not move alone but is related to no elite at the local level. Therefore, using qualitative analysis and literature and observation methods, this article discusses the construction of the elite, the legitimacy gained, and the existence of the elite in political politics in Aceh, both during the Dutch colonial period and Aceh as a part of Indonesia. This exploration shows that there are differences in the pattern of elite construction, the legitimacy obtained, and the existence of the elite in relations with the authorities. This difference is seen in the pattern of the boss changing local to local strongmen and vice versa. Likewise, the legitimacy is obtained by an elite based on rational law for charismatics and then back again to rational law. Hopefully, this study can add to the academic treasure of Aceh politics from a different perspective.